PEMBAGIAN WARIS SAMA RATA PERSPEKTIF HUKUM ISLAM - Asror, Nur (Jurnal Al-Wasith : Jurnal Studi Hukum Islam, 2023)
The distribution of inheritance basically adheres to the Al-Qur'an and hadith in accordance with the existing provisions in article 176 of the Compilation of Islamic Law. This research aims to determine the equal distribution of inheritance from the perspective of Islamic law, the opinion of Wahbah Az-Zuhaili in his book entitled Al-Fiqh al-Islamy Wa Adillatuh. This research uses library research methods (library research), namely a series of activities related to library data collection methods, reading and recording and processing research materials. The results of this research conclude that dividing inheritance equally is permissible, namely by using the takha>ruj method. Takha>ruj which means exit, terminologically usually means the exit of an heir by being replaced by another heir or not even being replaced, but someone giving up their share to another heir. The legal basis is the result of ijtihad (friends' atsarl) regarding events that occurred during the reign of Caliph Usmanl Bin Affan. The peaceful distribution of inheritance was based on the friends' atsarl as mentioned above.